Experimental evidences for reducing Mg activation energy in high Al-content AlGaN alloy by Mg(Ga) δ doping in (AlN)(m)/(GaN)(n) superlattice - Wang, Xiao (Sci Rep, 2017)
P-type doping in high Al-content AlGaN alloys is a main challenge for realizing AlGaN-based deep ultraviolet optoelectronics devices. According to the first-principles calculations, Mg activation energy may be reduced so that a high hole concentration can be obtained by introducing nanoscale (AlN)(5)/(GaN)(1) superlattice (SL) in Al(0.83)Ga(0.17)N disorder alloy. In this work, experimental evidences were achieved by analyzing Mg doped high Al-content AlGaN alloys and Mg doped AlGaN SLs as well as Mg(Ga) δ doped AlGaN SLs. Mg acceptor activation energy was significantly reduced from 0.378 to 0.331 eV by using Mg(Ga) δ doping in SLs instead of traditional doping in alloys. This new process was confirmed to be able to realize high p-type doping in high Al-content AlGaN.